Effect of JumpstartMD, a Commercial Low-Calorie Low-Carbohydrate Physician-Supervised Weight Loss Program, on 22,407 Adults - Sean Bourke; John Magaña Morton; Paul Williams (Journal of Obesity)
Background. Commercial weight loss programs provide valuable consumer options for those desiring support. Several commercial programs are reported to produce ≥3-fold greater weight loss than self-directed dieting. The effectiveness of JumpstartMD, a commercial pay-as-you-go program that emphasizes a low-to-very-low-carbohydrate real-food diet and optional pharmacologic treatment without prepackaged meals or meal replacement, has not previously been described. Methods. Completer and last observation carried forward (LOCF) of clinic-measured weight loss (kg) in 18,769 female and 3638 male JumpstartMD participants. Results. Completers lost (mean ± SE) 8.7 ± 0.04 kg, 9.5 ± 0.04% with 44.5 ± 0.5% achieving ≥10% weight loss at 3 months (mo, N = 14,999 completers); 11.8 ± 0.1 kg, 12.6 ± 0.1% with 66.4 ± 0.6% achieving ≥10% weight loss at 6 mo (N = 11,805); and 11.5 ± 0.2 kg, 12.0 ± 0.2% with 57.6 ± 0.9% achieving ≥10% weight loss at 12 mo (N = 8514). LOCF estimates were −6.5 ± 0.03 kg, −7.2 ± 0.03% with 27.1 ± 0.3% achieving ≥10% weight loss at 3 mo; −7.7 ± 0.04 kg, −8.5 ± 0.04% with 36.3 ± 0.3% achieving ≥10% weight loss at 6 mo; and −7.7 ± 0.1 kg, −8.4 ± 0.1% with 34.6 ± 0.3% achieving ≥10% weight loss after 12 mo. Frequent health coach meetings was a major determinant of weight loss, with women and men attending ≥75% of their weekly appointments losing 8.8 ± 0.04 and 11.9 ± 0.1 kg, respectively, after 3 mo, 13.1 ± 0.1 and 16.5 ± 0.3 kg after 6 mo, and 16.5 ± 0.3 and 19.4 ± 0.8 kg after 12 mo. Phentermine and phendimetrazine had a minor effect in women only at 1 (6.1% greater weight loss than untreated), 2 (4.1%), and 3 mo (1.2%), but treated patients showed longer enrollment than nontreated during the first 3 (females: +0.4 ± 0.01; males: +0.3 ± 0.04 mo), 6 (females: +1.1 ± 0.04; males: +1.0 ± 0.1 mo), and 12 mo (females: +2.7 ± 0.1; males: +2.4 ± 0.2 mo). JumpstartMD produced generally greater weight loss than published reports for other real-food and prepackaged-meal commercial programs and somewhat greater or comparable losses to meal replacement diets. Conclusion. A one-on-one medically supervised program that emphasized real low-carbohydrate foods produced effective weight loss, particularly in those attending ≥75% of their weekly appointments.